Kappa: Makhluk Mitologis Penjaga Sungai dalam Cerita Rakyat Jepang - Ida Ayu Laksmita Sari (Badan Pengembangan dan Pembinaan Bahasa, 2020)
This article discusses one of the Japanese mythological creatures in the youkai category, the kappa which is believed to be river guardians. Data is taken from the anthology of Japanese folklore Mangga Nippon Mukashi Banashi 101 edited by Sayumi Kawauchi. Folklore used as the object of research are two titles that were chosen selectively which are